The Last of the Strong Ones - Adimora-Ezeigbo, Akachi (Literamed Publications Ltd, 1996)
This engrossing saga is a recreation of old times in a town in eastern Nigeria. It takes the reader on a sensational sequence of journeys, sometimes allegorical, sometimes picturesque, into the heart and families in this close-knit four village community...
Keywords: Fiction